Guest Editorial Introduction to the Special Section on Mining Biomedical Data. - Tsymbal, A.
Research in data mining, also known as knowledge discovery in databases, aims at developing intelligent tools to automatically search large volumes of data for patterns. Biomedicine is a data-intensive field that forms one of the most important application domains in data mining and knowledge discovery. This special section contains 15 extended papers, focusing on mining of biomedical data, presented at the 18th IEEE International Symposium on Computer-Based Medical Systems, IEEE CBMS 2005, which was held on June 23?24, 2005, at Trinity College, Dublin, Ireland. This editorial first defines the field and then introduces the papers.
Keywords: Biomedical informatics; Data mining; Information systems; Relevance in research